2007
DOI: 10.1086/517613
|View full text |Cite
|
Sign up to set email alerts
|

A West Nile Virus Recombinant Protein Vaccine That Coactivates Innate and Adaptive Immunity

Abstract: A chimeric protein West Nile virus (WNV) vaccine capable of delivering both innate and adaptive immune signals was designed by fusing a modified version of bacterial flagellin (STF2 Delta ) to the EIII domain of the WNV envelope protein. This fusion protein stimulated interleukin-8 production in a Toll-like receptor (TLR)-5-dependent fashion, confirming appropriate in vitro TLR5 bioactivity, and also retained critical WNV-E-specific conformation-dependent neutralizing epitopes as measured by enzyme-linked immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
127
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(136 citation statements)
references
References 40 publications
7
127
0
2
Order By: Relevance
“…The deleted flagellin FliC ⌬174 -400 also retains adjuvant properties when administered s.c, suggesting that mucosal and dermal responses behave similarly and thus differ from the systemic response (data not shown). Studies with the S. typhimurium flagellin FljB (which harbors a similar deletion in the hypervariable region) have been recently performed with a view to using this type of molecule as an Ag carrier (14,21). Similar findings were obtained using the deleted flagellin FljB as a carrier for foreign Ags in s.c. immunization (21).…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…The deleted flagellin FliC ⌬174 -400 also retains adjuvant properties when administered s.c, suggesting that mucosal and dermal responses behave similarly and thus differ from the systemic response (data not shown). Studies with the S. typhimurium flagellin FljB (which harbors a similar deletion in the hypervariable region) have been recently performed with a view to using this type of molecule as an Ag carrier (14,21). Similar findings were obtained using the deleted flagellin FljB as a carrier for foreign Ags in s.c. immunization (21).…”
Section: Discussionmentioning
confidence: 72%
“…Various authors have reported that flagellins are potent systemic and mucosal adjuvants that elicit 1) serum and/or secretory Ab responses and 2) Th1 and Th2 cell responses to both the flagellins themselves and coadministered Ags (14,17,21,22).…”
Section: Deletion Of Flagellin's Hypervariable Region Abrogates Antibmentioning
confidence: 99%
“…Minke et al demonstrated that Recombitek Âź Equine West Nile, that expresses the prM/E genes of lineage 1 strain in a recombinant canarypox virus, could protect horses against a contemporary neurovirulent lineage 2 WNV isolate [123]. Finally, Yamshchikov et al reported that an attenuated non-epidemic West Nile virus strain of lineage 2 can be used as an effective vaccine against a virulent epidemic strain of lineage 1 in mice [124]. …”
Section: Vaccinationmentioning
confidence: 99%
“…116 As described above, as a consequence of the potent effects of flagellin on both the innate and adaptive limbs of the immune system, the protein has indeed been demonstrated to have potent adjuvantic effects in experimental vaccine constructs. [117][118][119][120][121][122] However, the safety profile of flagellin is yet to be unequivocally established. Of particular note, it has been observed that the administration of flagellin at doses comparable to or lower than that of bacterial LPS induces prominent local and systemic immune/inflammatory responses in vivo.…”
Section: Tlr5 Agonistic Flagellinmentioning
confidence: 99%